Integrating Wearable Devices into Patient Care: A Revolution in Health Care - Joshi, Mandar V. (Asian Journal of Pharmaceutics (AJP), 2024)
The integration of wearable devices into patient care has emerged as a transformative training in health care. These small, portable gadgets equipped with various sensors and data collection capabilities are reshaping the way health-care professionals monitor and manage patient health. This article explores the impact of wearable devices on patient care, highlighting their benefits and potential challenges. The benefits of incorporating wearable devices into health care are manifold. First, wearable devices unable to remote activity levels, and chronic condition in real time. This proactive readmissions and improving patient outcomes. Moreover, The HealthCare, Tailoring treatment plans to individual patients unique needs, wearable also Engage patient in their own health management, Faster ring empowerment and active participation furthermore. They play a vital role in preventing health-care patterns. Finally, wearable devices contribute significantly to medical research by collecting vast amounts of health data, potentially revolutionizing medical science.